2017
DOI: 10.1016/j.neurobiolaging.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity and the expression of orexin A and orexin B in aged female rhesus macaques

Abstract: Reduced activity has been linked to age-associated physiological changes but the underlying root cause is unclear. The goal of the present study was to compare the orexin neuronal system of old (23–29 years) female rhesus macaques with either active or sedentary 24-hour locomotor activity patterns. Using immunohistochemistry we counted the number of orexin A and orexin B neurons in the lateral hypothalamic area (LHA) of each animal. Overall, we observed no difference in the distribution pattern or number of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Scale bar in (d) = 500 μm and applies to all images. See list for abbreviations (e.g., Downs et al, 2007;Luna et al, 2017). In these primates, the main, zona incerta and optic tract clusters were reported, but the optic tract cluster extension was not observed in these studies (see Figure 9 for an example of orexinergic immunostaining in the human hypothalamus).…”
Section: A Novel Cluster Of Orexinergic Neurons In Apes? Evolutionary...mentioning
confidence: 86%
See 1 more Smart Citation
“…Scale bar in (d) = 500 μm and applies to all images. See list for abbreviations (e.g., Downs et al, 2007;Luna et al, 2017). In these primates, the main, zona incerta and optic tract clusters were reported, but the optic tract cluster extension was not observed in these studies (see Figure 9 for an example of orexinergic immunostaining in the human hypothalamus).…”
Section: A Novel Cluster Of Orexinergic Neurons In Apes? Evolutionary...mentioning
confidence: 86%
“…The distribution of orexinergic cell bodies and terminal networks have been described in a range of mammalian species (e.g., Davimes et al, 2017; Dell et al, 2012; Dell, Karlsson, Patzke, Spocter, Siegel, & Manger, 2016; Dell, Patzke, Spocter, Bertelsen, Siegel, & Manger, 2016; Dell, Kruger, Pettigrew, & Manger, 2013; Dell, Patzke, Spocter, Siegel, & Manger, 2016; Gravett, Bhagwandin, Fuxe, & Manger, 2011; Iqbal, Pompolo, Sakurai, & Clarke, 2001; Khorooshi & Klingenspor, 2005; Kruger, Dell, Pettigrew, & Manger, 2010; Malungo et al, 2020; Nixon & Smale, 2007; Yamamoto et al, 2006; Zhang, Sampogna, Morales, & Chase, 2002), including strepsirrhine primates (Calvey et al, 2015) and humans (Elias et al, 1998; Moore, Abrahamson, & van den Pol, 2001; Thannickal et al, 2018; Thannickal, Moore, et al, 2000; Thannickal, Neinhuis, & Siegel, 2009). However, the detailed mapping and nuclear parcellation of orexinergic neurons has not been undertaken in other species of catarrhine (apes and Old World monkeys) or platyrrhine (New World monkeys) primates, although the presence of these neurons has been noted and quantified in Macaca mulatta (e.g., Downs et al, 2007; Luna, Brown, Eghlidi, Kohama, & Urbanski, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, BDNF, a key regulator of synaptic plasticity and transmission, has been suggested to induce the expression of miR-132 [ 216 ]. The expression of the miR-132/212 family members has been downregulated in early AD [ 194 , 217 ] and it was suggested that miR-132 targets the gene coding for methyl CpG binding protein 2 (MeCP2), responsible for increasing BDNF levels in the brain tissue. Kawashima et al demonstrated that the BDNF-dependent increase in the expression of postsynaptic proteins could be decreased by inhibiting miR-132 function [ 217 ].…”
Section: Epigenetic Alterations In Alzheimer’s Diseasementioning
confidence: 99%
“…Orexin neurons projected to the LC and TMN were mainly involved in wakefulness/arousal populations), and those projected to NAc and VTA regulate reward populations (Iyer et al 2018). A few results were seen for the structure and distribution of orexin A neurons shown from three-dimensional morphology, which was just limited in two-dimensional space (Luna et al 2017;Cheng et al 2003). In the current study, we compared the expression, population, and morphology by different experiments including tissue optical clearing tracing, deep imaging, and three-dimensional reconstruction, determining increased population and more extensive distribution in the AD model.…”
Section: Discussionmentioning
confidence: 99%